The Antinociceptive Efficacy of HWTX-I Epidurally Administered in Rheumatoid Arthritis Rats - Wen tao, Z.; Gu yang, T.; Ying, R.; Mao cai, W.; Lin, L.; Chi miao, L.; Peng, H.; Jia Qin, C. (International Journal of Sports Medicine, 2011)
Rheumatoid arthritis (RA) is one of the inflammatory kinds of arthritis in the clinical situation, and cytosolic Ca2+ overload has been proposed as one of the primary factors for many inflammatory cells activation, which lead to relative enzymes and inflammatory factors release. It is therefore accepted that Ca2+ channel blockers can protect joint injury from inflammation. In the present study we investigated the possible molecular mechanism of the antinociceptive efficacy of HWTX-I, a spider peptide toxin blocking Ca2+ channels, on the rat rheumatoid arthritis model. Our study demonstrates that HWTX-I can relieve pain in the inflammatory joints and eliminate arthrocele to some degree. Moreover, HWTX-I can also decrease the concentration of tumour necrosis factor α (TNF-α) and increase the concentration of interleukin 4(IL-4) and interleukin 10(IL-10) in rat’s serum. HWTX-I can also decrease the mRNA expression level of related factors of TNF-α, interleukin 1β (IL-1β) and interleukin 6(IL-6) in inflammatory pathways in rheumatoid arthritis. Therefore, the present results show that the epidural administration of HWTX-I is effective in antinociception in the rat model of rheumatoid arthritis, which may act through its inhibition on certain inflammatory pathways.
Keywords: HWTX-I; rheumatoid arthritis; calcium channel blocker; antinociception